Effect of the Physicochemical Modification on Bismuth-doped Zinc Oxide in the Anisotropic Orientation of Liquid Crystal Molecules. (8th April 2020) - Jeong, Hae-Chang; Kim, Eun Mi; Heo, Gi-Seok; Lee, Ju Hwan; Won, Jong Hoon; Kim, Dong Hyun; Lee, Dong Wook; Han, Jeong-Min; Kim, Tae-Wan; Seo, Dae-Shik
Abstract : Alignment of liquid crystals by ion-beam (IB) irradiated bismuth-doped zinc oxide (BZO) films was investigated. The BZO alignment layer was deposited using a simple solution process, and IB irradiation of the BZO was used to induce surface-alignment of LC molecules uniformly. Solution-processed thin films have numerous advantages, including low manufacturing cost, simplicity of fabrication, and high productivity. IB irradiation of the BZO film induces a drastic improvement in the uniformity of the BZO surface and creates physico-chemical modifications that preserve the anisotropic characteristics of the surface, thereby unidirectionally aligning the LC molecules.